Athletes’ (Anti) Doping Knowledge: A Systematic Review - Dina Listiani; Fadilah Umar; Slamet Riyadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This systematic review critically examines the scope of athletes’ knowledge on anti-doping regulations, focusing on literature from 2018 to 2022. Adhering to PRISMA guidelines, we scrutinized electronic databases including Scopus, ScienceDirect, PubMed, and Google Scholar, yielding 4,009 articles, with 17 meeting our criteria for in-depth analysis. Our findings reveal a significant disparity in anti-doping awareness across different sports disciplines and regions. Notably, the review highlights that while some athletes demonstrate a comprehensive understanding of anti-doping rules, a considerable portion remains unaware of crucial aspects, potentially leading to inadvertent doping violations. The synthesis of the selected studies indicates that current educational programs on anti-doping are insufficiently tailored to address the diverse needs of athletes worldwide. Consequently, we advocate for the development of targeted educational interventions that align with the varying levels of existing knowledge among athletes. By enhancing the specificity and reach of anti-doping education, we aim to empower athletes to uphold the integrity of sports and adhere to the World Anti-Doping Code, thereby mitigating the risks of both intentional and unintentional doping.